Three hundred Aesop$1 (Bs fables :s Translated by George Fyler Townsend - Aesop; Townsend, George Fyler, 1814-1900 (Salt Lake City, UT : Project Gutenberg, 2008)
"Three Hundred Aesop's Fables" by Aesop is a collection of fables originating between 620 and 564 BCE. These timeless tales feature talking animals, plants, and humans navigating moral dilemmas and life lessons. Originally part of oral tradition, the stories were collected centuries after Aesop's death and grew to include works from diverse sources across cultures. Each brief narrative offers wisdom through simple scenarios, often concluding with explicit morals that have shaped ethical thinking for millennia. (This is an automatically generated summary.)
See also the early PG version #28, and comprehensive versions PG#11339 tr. by V. S. Vernon Jones, and illustrated PG#18732.
Wikipedia page about this book: https://en.wikipedia.org/wiki/Aesop%27s_Fables
Release date is 2008-06-25
David Widger
Keywords: Fables, Greek -- Translations into English; Aesop's fables -- Translations into English